APPLYING INQUIRY LEARNING MODEL ASSISTED MATHEMATICS MICROSOFT APLICATION TO IMPROVE CREATIVITY AND LEARNING ACHIEVEMENT - Yessa Kurniawan; Nina Kurniah (DIADIK, 2019)
This reasearch aimed to Describe creativity of student learning in mathematics lesson grade XI SMK Negeri 3 Lebong, Describe student learning achievement in mathematics lesson grade XI SMK Negeri 3 Lebong, Describe efectivity applying inquiry learning model to improve student learning achievement in mathematics at SMK N 3 Lebong. The kind of this reasearch subject of this experiment is student grade XI TKJ 2 SMK N 3 Lebong as PTK class, then student grade XI TKJ 1 SMK N 3 Lebong as experiment class and student grade XI Accountancy SMK N 3 Lebong as control class. Class selection is chosen propositive random sampling. This data is collected using teacher observation sheet, student observation sheet, and student learning achievement test. After t-tes it can be concluded that by using inquiry learning model be able to improve creativity and student learning achievement.